Reports and actions developed by nurses in the reach of equity in health - Freitas, Kerma Márcia de (2021)
Objective: The present study describes reports and actions developed by nurses to achieve health equity in primary care services. Methodology: Qualitative research with a descriptive nature was carried out in a municipality of Ceará State, Brazil, in 2020. The participants were six nurses from the family health strategy working in health units, who had a postgraduation degree in family health/public health. Data collection was performed through semi-structured interviews analyzed using the content analysis technique and thematic modality and interpreted in the light of literature. Results: Three thematic categories emerged from this process: Conceptual approaches on equity and inequity in health; Health equity in the praxis of primary care; and Perceptions on equitable policies and academic-professional training. The participants relate equity to equality-justice and recognize that it is crucial for effective user access in addition to describing nursing actions centered on the assessment of vulnerabilities, which promote the achievement of this principle. However, it is emphasized the importance of broadening the interpretation of the social scope that encompasses health policies, the guidelines ruling the scope of this principle. Conclusion: Therefore, it is imperative to resume dialogues and actions on the qualification of health practices resulting from continuing education in the work process in primary care.